2016
DOI: 10.1080/21505594.2016.1229727
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell analyses reveal an attenuated NF-κB response in theSalmonella-infected fibroblast

Abstract: The eukaryotic transcriptional regulator Nuclear Factor kappa B (NF-κB) plays a central role in the defense to pathogens. Despite this, few studies have analyzed NF-κB activity in single cells during infection. Here, we investigated at the single cell level how NF-κB nuclear localization - a proxy for NF-κB activity - oscillates in infected and uninfected fibroblasts co-existing in cultures exposed to Salmonella enterica serovar Typhimurium. Fibroblasts were used due to the capacity of S. Typhimurium to persis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 58 publications
1
27
0
Order By: Relevance
“…Expanding upon a recent study of the TLR response to lipid A (Gottschalk et al, 2016), our work confirms that engagement of MAPK signaling is a universal signature of an escalation in the threat to the host cell, be it high doses of PAMPs, infection, or bacterial replication. Identifying the role of MAPKs, and perhaps more importantly, the MAPK-NF-kB combination, in discrimination of the infection threat level, also adds a critical new dimension to the recent finding that NF-kB activation dynamics are altered in Salmonella-infected fibroblasts (Ramos-Marquè s et al, 2017). Furthermore, JNK signaling was a signature both of cells with replicating S. typhimurium and those that can secrete effectors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Expanding upon a recent study of the TLR response to lipid A (Gottschalk et al, 2016), our work confirms that engagement of MAPK signaling is a universal signature of an escalation in the threat to the host cell, be it high doses of PAMPs, infection, or bacterial replication. Identifying the role of MAPKs, and perhaps more importantly, the MAPK-NF-kB combination, in discrimination of the infection threat level, also adds a critical new dimension to the recent finding that NF-kB activation dynamics are altered in Salmonella-infected fibroblasts (Ramos-Marquè s et al, 2017). Furthermore, JNK signaling was a signature both of cells with replicating S. typhimurium and those that can secrete effectors.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, while an immune cell could co-opt signaling pathways beyond the TLRs to transmit contextual information about a given bacterial stimulus, there is increasing evidence that a cell could also use the dynamics of TLR signaling proteins for this purpose. For example, S. typhimurium infection of fibroblasts has been shown to reduce NF-kB dynamics in infected cells via the secretion of effectors (Ramos-Marquè s et al, 2017), while Cryptococcus neoformans infection of macrophages was found to increase NF-kB signaling by modulating the negative feedback response (Hayes et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Similar observations have recently been found in S. Typhimurium-infected fibroblasts, in which infected and uninfected cell subpopulations were sorted and examined separately for analysis of the NF-kB defense response. 25 Third, and most importantly, the authors were able to correlate the bimodal induction of type I INF response genes in infected macrophages with differences in the activity of PhoP-PhoQ regulatory system in intracellular bacteria. This latter finding was possible by FACS sorting of the infected macrophages populations using a fluorescent reporter to an IFNstimulated response element (ISRE).…”
Section: The Advent Of Single-cell Analyses and Rna-seq Technologies:mentioning
confidence: 91%
“…Electron or classical fluorescence microscopy require the use of fixed samples that preclude an observation in a dynamic mode. This recent study 5 analyses at the single cell level the dynamics of the NF-kB pathway during an infection. Using a software that automatically defines cell segmentation based on the Hoechst nucleus staining while tracking the p65-GFP signal, they were able to calculate the nuclear to cytoplasmic ratio of the GFP intensity, which was then exploited as a read-out of NF-kB activation.…”
mentioning
confidence: 99%
“…Over the last number of years, the number of publications reporting such an approach has increased with applications in a wide variety of fields including bacterial replication, 1,2 bacterial cell morphology, 3 and deformation of red blood cells. 4 In this issue of Virulence Ramos-Marques et al 5 combine up-to-date technologies and single cell analysis to obtain an insight of how bacterial pathogens interact with host cells.…”
mentioning
confidence: 99%